INTEGRATION OF ICT BY THE USE OF THE YOODLI ARTIFICIAL INTELLIGENCE ON STUDENTS’ SPEAKING SKILL - Pricilia, Gabby Maureen; Irmayana, Aprida; Rahmansyah, Habib; Iskandar Lubis, Wildan (Institut Pendidikan Tapanuli Selatan, 2025)
The aim of this research is to know the integration of ICT on students’ speaking learning by the use of the Yoodli AI. The research was conducted by using mixed method explanatory sequential design with 12 students as the sample taken by total sampling. Questionnaire and test were using in collecting the data. Based on the data analysis, it was seen that Yoodli AI helped students in speaking. The mean score of students speaking skill before using Yoodli AI was 64.4 categorized